Agricultural policies in India: producer support estimates 1985-2002 - Mullen, Kathleen; Orden, David; Gulati, Ashok (International Food Policy Research Institute, 2005)
Since the early 1990s, India has undergone substantial economic policy reform and economic growth. Though reforms in agricultural policy have lagged those in other sectors, they have nonetheless created a somewhat more open economic orientation. In this study, we evaluate the protection and support versus disprotection of agriculture in India. Our methodology involves examining market price support (MPS) for eleven crops, the expenditures on input subsidies benefiting farmers (for fertilizer, electricity and irrigation), and product-specific and total producer support estimates (PSEs) over the period 1985-2002. We draw on the extensive price-comparison and subsidy-measurement data sets and analysis developed earlier by Gulati and his co-authors, often using disaggregated analysis for representative surplus and deficit states. This allows us to explore how key cost adjustments impact the results. Overall, our results indicate that support for agriculture in India has been counter-cyclical. Support for agriculture has been rising when world prices are low (as in the mid 1980s and 1998-2002) and falling when world prices are high (as in the early and mid 1990s). Our results demonstrate the increased importance of budgetary payments for input subsidies in agriculture in recent years. Yet, in the aggregate for both price support and budgetary expenditures over the period 1985-2002 the counter-cyclical dimension of agricultural policy dominates a clear trend of movement from disprotection towards protection. Using different variants of MPS and PSE measurment we have extended earlier analysis to demonstrate the impact of key assumptions on the calculations. These assumptions we argue are important to consider. For example, in the standard approach, the MPS for the covered commodities is “scaled up” based on the share of the covered commodities in the total value of production. If the commodity coverage is less than complete, as is often the case, the scaling up procedure leads to a total MPS of greater absolute value than the MPS for the covered commodities. This can result in PSEs of different sign than the non-scaled up version but is inappropriate unless market price support for the commodities not covered is similar to that of the covered commodities. Furthermore, we find that the standard procedure of computing the MPS through a comparison of the domestic price to an adjusted reference price based on observed imports or exports can be problematic. This happens when trade volumes are relatively small. In such a scenario a reference price based on observed imports or exports can lead to misleading conclusions. To address the reference price issue, we follow Byerlee and Morris (1993). Essentially the approach adopted is to compute the level of protection or disprotection based on a counterfactual reference price chosen on economic criteria i.e. the adjusted reference price that would exist in the country if the policy interventions were removed. The relevant price can either be the autarky equilibrium price or the import or export adjusted reference price depending on the relationship among these prices. We apply this modified procedure for six crops (wheat, rice, corn, sorghum, sugar and groundnuts). The choice of the crops is dictated by the fact that India has been near self-sufficiency and there have been changes in the direction of trade over the period of analysis. The magnitudes of estimated support for agriculture obtained in this paper are important for several reasons. The estimates confirm that high levels of subsidies were required for India to export wheat or rice in recent years, a conclusion reached by several other studies. However, we report less disprotection of Indian agriculture in the 1990s than in earlier studies. Partly this difference is explained by the modified procedure for choice of a reference price. A large component of this difference can be accounted for by whether or not the scaling up procedure is invoked. There are also fertile areas for future research. Estimates of adjustment costs used in domestic-to-border price comparisons, such as transportation and processing costs or marketing margins, are crucial variables in the analysis and merit being re-examined and further updated. Resolving what are the most reasonable assumptions about reference prices, or extending the analysis to additional crops and livestock to reduce uncertainty in future assessments will also contribute to fuller understanding of the net stance of policy toward agriculture and how it has evolved over time